دور الدولة في توفير العقار الاقتصادي لإنشاء المؤسسات الصغيرة والمتوسطة - بوشوشة, محمد (جامعة الوادي - University of Eloued, 2018)
يشكل العقار الاقتصادي عنصرا مهما لأي استثمار، وذلك لعدة اعتبارات أهمها: أي استثمار يجب أن يتوفر على مقر معين وذلك من أجل إجراء مختلف التعاملات ذات الصلة مع هذا الاستثمار، كذلك يشكل العقار من أهم التكاليف التي يمكن أن يتحملها المستثمر لإنجاز استثماره لارتفاع تكلفة حيازته، نتيجة لذلك اعتمدت الجزائر عدة إجراءات وسياسات لتسهيل حصول المستثمرين وخاصة في قطاع المؤسسات الصغيرة والمتوسطة على العقارالاقتصادي لتجسيد استثماراتهم، لكن رغم ذلك يبقى العقار يشكل هاجسا للمستثمرين، كذلك كان هذا العنصر السبب الأساسي في تخلي العديد من المستثمرين عن تحقيق مشروعاتهم الاستثمارية. The economic real estateis an important element for anyinvestment, because of severalconsiderations, the most important of whichis: Anyinvestment must beavailable to a particularheadquarters in order to conductvarious transactions related to thisinvestment, as well as the propertyis the most important coststhatcanbe borne by the investor to complete the investment to the highcost of possession, As a result, Algeria has adoptedseveralmeasures and policies to facilitateinvestors' access to real estate, particularly in the small and medium-sizedfirmssector, to realizetheirinvestments. However, the real estateremains a concern forinvestors.
The role of the state in providingeconomic real estate for the small and medium firms
مقال
Keywords: العقار، المؤسسة الصغيرة والمتوسطة، العقار الاقتصادي، الامتياز العمومي، الامتيازات الجبائي.; real estate, small and medium firm,economic real estate